Bluebirds and their survival - Davis, Wayne Harry, 1930-; Roca, Philippe, 1956- (Lexington, Ky. : University Press of Kentucky, 1995)
A fascinating guide which tells you what you need to know to bring more bluebirds into your life In this detailed how-to book, bluebird expert Wayne H. Davis tells how to attract and care for this beautiful and gentle bird and offers solutions to the most common bluebird problems. Since bluebirds are almost entirely dependent on people for providing nesting sites, the book contains plans for erecting a structure that will attract bluebirds to a safe habitat. Instructions for building and maintaining a ""bluebirds trail, "" complete with drawings of various bluebirds houses and guards against pr
Black Bears (Ursus americanus)Squirrels and Chipmunks; Weasels; Red Fox (Vulpes vulpes); Hawks and Other Birds; 10. A Bluebird Trail; 11. Building Your Own; Tools; Materials; Choosing Designs; Building Boxes, Feeders, Traps, and Guards; 12. Photographing Birds; The Blind; Equipment; Setting Up Your Shots; Birds in Flight; 13. Troubleshooting; Appendix: Organizations and Suppliers; Literature Cited; Index
Includes bibliographical references (pages 145-149) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Bluebirds; Bird attracting; Bluebirds -- Housing; Birds -- Conservation; Merlebleus; Attraction des oiseaux; Merlebleus -- Logement; Oiseaux -- Protection; NATURE -- Environmental Conservation & Protection; Bird attracting; Birds -- Conservation; Bluebirds; Electronic books